Clinical applications of imaging disease burden in multiple sclerosis: MRI and advanced imaging techniques. (March 2012) - Riley, Claire; Azevedo, Christina; Bailey, Mary; Pelletier, Daniel
This review will address the critical role of radiographic techniques in monitoring multiple sclerosis disease course and response to therapeutic interventions using conventional imaging. We propose an algorithm of obtaining a contrast-enhanced brain MRI 6 months after starting a disease-modifying therapy, and considering a gadolinium-enhancing lesion on that scan to indicate suboptimal response to therapy. New or enlarging T2 lesions should be followed on scans at 6-month intervals to assess for change, and the presence of one or more enhancing lesions on a 6- or 12-month scan, or two or more new or enlarging T2 lesions on a 12-month scan should prompt consideration of therapy change. New techniques such as PET imaging, magnetic resonance spectroscopy, magnetic resonance relaxometry, iron-sensitive imaging and perfusion MRI will also be overviewed, with their potential roles in monitoring disease course and activity.